Exploring the consumer profile of students: An economic approach - Mihaela Brindusa Tudose (CES Working Papers, 2019)
The study presents the main features of consumer behavior patterns from an economic perspective (Marshallian, Pavlovian, Freudian, Veblenian, and Hobbesian models). Based upon the qualitative analyses (which have used the information from two focus groups and the student's statement related to the importance of various categories of expenditure, valued on a 5-step scale) and quantitative analyses (which aimed the actual student allocations per expenditure category), the consumer profile of the students learning in the city of Iasi was achieved. The results of the qualitative research reveal that the student's consumer behavior profile corresponds to the Freudian model (based upon attitudes, the intensity of needs, opinions and motivations), and the results of the quantitative analysis reveal that the student's consumer behavior profile corresponds to the Veblenian model (based upon the desire to obtain a certain prestige rather than the motivation to satisfy needs). The study confirms the results of previous research, according to which the rationality of decisions to meet individual needs is strongly influenced by circumstances.
Keywords: 330; students; consumer behavior; consumption needs; utility; behavior patterns